George's Secret Key to the Universe - Hawking, Lucy; Hawking, S. W. (Stephen W.); Galfard, Christophe; Parsons, Garry (New York : Simon & Schuster Books for Young Readers, 2007)
Follows the adventures of a young boy and his neighbor friend as they travel through a computer portal into outer space, where they explore such mysteries as black holes and the origins of the universe, while trying to evade an evil scientist.
008 up.
Accelerated Reader AR